Diagnóstico da gestão dos resíduos sólidos urbanos nos municípios da Bacia Hidrográfica do Rio do Índio - Estado do Paraná - Albertin, Ricardo Massulo (2011)
Disordered urban growth, without appropriate planning for the urban systems, results in environmental, sanitary, social and economic problems. Among them, urban solid waste has become one of the greatest problems faced by the Brazilian public administration. In such context, this present study has had the objective of diagnosing the management of urban solid waste in the tows of "Rio do Índio" hydrographic basin, in the state of Paraná, Brazil. The methodological procedures observed the characterization of the researched towns, the application of questionnaires, technical in loco visitations and the evaluation of final disposition Units of domiciliary and commercial waste, utilizing, in order to accomplish so, the Waste Landfill Quality Standards (Portuguese: IQR - Índice de Qualidade de Aterro de Resíduos). The obtained results demonstrated that the administrative structure for management of waste contemplates the utilization of 187 people, working as direct remunerated workers. The responsibility for the management of waste is performed by direct public administration, as well as by outsourced companies. The researched tows generated, in average, 1.813 ton/month of domestic and commercial solid waste, whose per capita generation average is 0,518 kg/inhab./day. Conventional waste collection is present for 100% of urban houses. About selective collection, it was observed the existence of 41 collectors of recyclable materials, but only the towns of Cianorte/PR and São Tomé/PR have implanted programs. Construction and demolition waste are collected by the municipal public administration and also by outsourced private companies. The final disposition of these residues occurs in irregular disposal areas, as well as in inert waste landfill areas. For the industrial waste management, it was observed that most of the towns do not perform its collection, which becomes the generator?s responsibility. Special waste does not observe the utilization of management programs, but only a few initiatives. Regarding the final disposition of domiciliary and commercial waste, this study enabled us to conclude that 80% of generated residues are disposed in form of adequate sanitary landfill, while 20% of it is disposed in form of inadequate controlled landfill or waste yards.